Short‐term outcomes of robotic lobectomy versus video‐assisted lobectomy in patients with pulmonary neoplasms - Tian‐Yu Sun; Chu‐Long Xie; Zihui Tan; Ji‐Bin Li; Mu‐Zi Yang; Hao‐Xian Yang (Thoracic Cancer, 2023)
Abstract Background To explore whether robotic lobectomy (RL) is superior to video‐assisted lobectomy (VAL) in terms of short‐term outcomes in patients with pulmonary neoplasms. Methods From January 30, 2019 to February 28, 2022, a series of consecutive minimally invasive lobectomies were performed for patients with pulmonary neoplasms. Perioperative outcomes such as operation time, blood loss, dissected lymph nodes (LNs), surgical complications, postoperative pain control, length of postoperative stay in hospital, and total cost of hospitalization were compared. Results A total of 336 cases including 173 RLs and 163 VALs were enrolled. Baseline characteristics were comparable between groups. RLs were associated with shorter operation time (median [interquadrant range, IQR], 107 min [90–130] vs. 120 min [100–149], p < 0.001), less blood loss (median [IQR], 50 mL [30–60] vs. 50 mL [50–80], p = 0.02), and lower blood transfusion rate (3.5% vs. 9.8%, p = 0.02) compared with VALs. More LNs were harvested by the robotic approach (median [IQR], 29 [20–41] vs. 22 [15–45], p = 0.04). The incidences of conversion, major postoperative complications, extra analgesic usage, and postoperative length of stay were all comparable between the RL and VAL groups. As predicted, the total cost of hospitalization was greater in the RL group (median [IQR], $16728.35 [15682.16–17872.15] vs. $10713.47 [9662.13–11742.15], p < 0.001). Conclusion RL improved surgical efficacy with shortened operative time, less blood loss, and more thorough LN dissection compared with VAL, compromised by higher cost.